Investigation of laminar to turbulent transition phenomena effects on impingement heat transfer - İşman, Mustafa Kemal; Morris, Philip J.; Can, Muhiddin (Springer, 2016)
Turbulent impinging air flow is investigated numerically by using the ANSYS-CFXA (R) code. All computations are performed by considering three-dimensional, steady, and incompressible flow. Three different Reynolds averaged Navier-Stokes (RANS) turbulence models and two Reynolds stress models (RSM's) are employed. Furthermore three different laminar to turbulent transition (LTT) models are employed with the shear stress transport (SST) and the baseline (BSL) models. Results show that predictions of the SST and two RSM's are very close each other and these models' results are in better agreement with the experimental data when all Reynolds numbers used in this study are considered. Secondary maxima in Nusselt number can be seen only if the LTT formula is employed with SST and BSL models.
Keywords: [No Keywords]